Media use, political knowledge and political efficacy among youth in Malaysia. - Ting, Su Hie (2022)
Youth become disenfranchised because they feel disconnected from events and movements in the community and the country, and they cannot be engaged to move along with the national agenda. To deal with youth disenfranchisement, some governments have embarked on programmes to instil citizenship values through the school and the mass media (e.g., Singapore, Hong Kong, Malaysia). Political knowledge has a crucial impact on youth online political participation in Malaysia (Ridzuan et al., 2021) but the question is – what are the sources of their political knowledge? Youths are an important subject to study at this point in time in the sociopolitical landscape to find out whether they are concerned about current issues affecting the country, when translated to everyday concerns. The present study examined media use, political knowledge, and political efficacy among youth in Malaysia. The survey involved 590 youth aged 18-40 from Malay, Indigenous, Chinese, and Indian ethnic backgrounds, of which 91% had lower socio-economic status. As for educational background, 59% had completed Form Six or Diploma and 18% had degree qualifications. There was a balanced number of participants from urban and urban locations. The questionnaire had items on media use (5-point Likert scale), political knowledge on 10 concepts or issues affecting the Malaysian public (3 levels), and political efficacy (5-point Likert scale). Data collection was by means of printed questionnaires distributed by the researcher and research assistants. The questionnaire data were keyed into an Excel sheet before subsequent analysis via means and standard deviation. Pearson correlation tests were also run to determine if there were significant relationships among the three variables. There were no significant correlations among the three variables (media use, political knowledge, and political efficacy). However, it is still important to know the characteristics of the youth with respect to these three variables because they reveal the level of political knowledge, the sources by which the youth acquire their political knowledge, and their perceived ability to change and influence political decisions in the country. The results on media use showed that moderate use of online and printed media to access news on community or national issues. The youth preferred online newspapers to printed newspapers. The regularity of reading magazines and blogs for news is below average. Sometimes they watched discussions on community or national issues on YouTube and television, but their preference is towards YouTube. The present-day youth are more keen on online sources of news. An interesting phenomenon is that they may not get the news directly from the newspaper websites, but rather the news items are forwarded to them by their social media contacts. This shows how social media is indirectly an important source of political news but it is their peers and social contacts who make the selection of what constitutes interesting news to spread. Next, the results on political knowledge are described. The participants in the study were presented with 10 current issues to find out whether they recognised the term and the political context of the issue. The youth were the most aware of the BR1M or “Bantuan Rakyat 1 Malaysia” programme (translated as Help Citizen 1 Malaysia). This was a programme introduced by the Barisan Nasional government to provide financial help to those with a monthly income of below RM4,000 (USD$950). The youth knew about BR1M because cash handouts of RM100-RM200 were given to students, and many retired people, single parents and those with lower income have benefitted from the programme. The other top two issues that Malaysian youth were familiar with were petrol price and minimum wage. The youth were also very aware of petrol price fluctuations and its implications on their lives. Half of the participants recognised the term and knew its political context. Another 36% recognised the term but were unsure of its political context while a small percentage (8%) did not know what the term referred to. The Malaysian government subsidises the petrol price. The Pakatan Harapan government which ruled Malaysia in 2018-2020 knew the importance of petrol subsidy to the citizens and announced plans in 2019 to introduce petrol subsidy. However, the programme to provide the lower income group with a fixed monthly subsidy rate was dropped in July 2020. Minimum wage was introduced in Malaysia in July 2012, with the Minimum Wages Order 2012 taking effect on 1 January 2013 (Lee, 2021). The wage rates differed for West Malaysia (RM900/month) and East Malaysia (RM800). As of 1 May 2022, the minimum wage is RM1,100 - RM1,200 per month depending on places of employment. Judging from the familiarity of the top second and third issues to the youth of Malaysia, it is clear that the government of the day also knew how to capitalise on the everyday concerns of the people to win their support. The issue that is least known by the youth was Transformasi Nasional 2050 (TN50, National Transformation 2050). This was also an initiative of the Barisan Nasional government scheduled for implementation in 2020-2050. The engagement with youth to find out their aspirations for the nation started in 2017 and the TN50 policy documents were supposed to be released in 2020. However, when the Pakatan Harapan government took over the rule of Malaysia in May 2018, the TN50 plans were cancelled. This is probably why the youth did not have much idea of what the transformation of the country entailed. Finally, the results on political efficacy show that the youth were more confident about engaging in political action than in discussing important political issues. They youth felt that they were confused about politics, irrespective of how much they read or talked about the issues. In the eyes of the Malaysian youth in the present study, politics is complex and there are many hidden motives for actions of politicians and political parties. However, their perceived confidence to participate in political action such as rallies, petititons and protests indicate that they are a force to be reckoned with. The findings contradict some existing findings on the existence of a relationship between political knowledge and online political participation among Malaysia youth. The study indicate that online newspapers and the social media are means to engage youth to move along with the national agenda. It may possibly bring more impact to youth than school citizenship programmes.